2004
DOI: 10.1111/j.1467-842x.2004.tb00442.x
|View full text |Cite
|
Sign up to set email alerts
|

The self‐reported health status of prisoners in New South Wales

Abstract: Objective: To describe the physical health of the New South Wales prisoner population. Design:Cross-sectional random sample of adult men and women prisoners. Similarly, methadone maintenance was more common among women than men (39% vs. 13%; p<0.001). Conclusion:Men and women prisoners in NSW have multiple chronic health conditions. While not desirable, incarceration presents an opportunity to initiate treatment to improve the health of this disadvantaged group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
3
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 14 publications
8
59
3
10
Order By: Relevance
“…Prisoners' poor health status as well as a high prevalence of mental disorders and mental health deprivation have been reported in various studies [3,5,8,[55][56][57][58][59]. Furthermore, it is confirmed that prisoners report a deterioration of their health status during their detention [3,30,[60][61][62].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Prisoners' poor health status as well as a high prevalence of mental disorders and mental health deprivation have been reported in various studies [3,5,8,[55][56][57][58][59]. Furthermore, it is confirmed that prisoners report a deterioration of their health status during their detention [3,30,[60][61][62].…”
Section: Discussionmentioning
confidence: 70%
“…The expanding detainment rates directly affect inmates' overall health status [3]. The high commonness of prisoners' health related problems seems to be ascribed to various socio-economic characteristics for example destitution, low wage and low training level [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Prisoners' poor health status as well as the high prevalence of mental health deprivation and mental disorders has been also reported in various studies [21][22][23][24][25][26][27][28]. Moreover, dissatisfaction with the detention conditions was also reported in a Greek study focused on male prisoners as well as in the international literature [11,29,30].…”
Section: Discussionmentioning
confidence: 84%
“…(Beck et Maruschak, 2001), une différence importante se creuse entre la prévalence observée chez les hommes (9 %) et les femmes (22 %). La même tendance a été observée dans les prisons de la Nouvelle-Gallesdu-Sud, en Australie, soit : 13 % chez les hommes et 25 % chez les femmes (Butler et al, 2004).…”
Section: Caractéristiques Des Usagersunclassified